Creatine kinase and its isoenzymes in the serum and cerebrospinal fluid of healthy canines - Kopanke, Jennifer H (Veterinary clinical pathology, 2023)
© 2023 The Authors. Veterinary Clinical Pathology published by Wiley Periodicals LLC on behalf of American Society for Veterinary Clinical Pathology.